Evidence That Calcium Entry Into Calcium-Transporting Dental Enamel Cells Is Regulated by Cholecystokinin, Acetylcholine and ATP - Nurbaeva, Meerim K.; Eckstein, Miriam; Devotta, Arun; Saint-Jeannet, Jean-Pierre; Yule, David I.; Hubbard, Michael J.; Lacruz, Rodrigo S. (Frontiers in Physiology, 2018)
Enamel is formed by specialized epithelial cells which handle large quantities of Ca2+ while producing the most highly mineralized tissue. However the mechanisms used by enamel cells to handle bulk Ca2+ safely remain unclear. Our previous work contradicted the dogma that Ca2+ is ferried through the cytosol of Ca2+-transporting cells and instead suggested an organelle-based route across enamel cells. This new paradigm involves endoplasmic reticulum (ER)-associated Ca2+ stores and their concomitant refilling by store-operated Ca2+ entry (SOCE) mediated by Ca2+ release activated Ca2+ (CRAC) channel. Given that Ca2+ handling is maximal during the enamel-mineralization stage (maturation), we anticipated that SOCE would also be elevated then. Confirmation was obtained here using single-cell recordings of cytosolic Ca2+ ([Ca2+]cyt) in rat ameloblasts. A candidate SOCE agonist, cholecystokinin (CCK), was found to be upregulated during maturation, with Cck transcript abundance reaching 30% of that in brain. CCK-receptor transcripts were also detected and Ca2+ imaging showed that CCK stimulation increased [Ca2+]cyt in a dose-responsive manner that was sensitive to CRAC-channel inhibitors. Similar effects were observed with two other SOCE activators, acetylcholine and ATP, whose receptors were also found in enamel cells. These results provide the first evidence of a potential regulatory system for SOCE in enamel cells. Highlighting this ER-based mechanism supports the notion that Ca2+ could transit across the ameloblasts via the ER. Our findings also implicate enamel cells as a new physiological target of CCK and raise the possibility of an auto/paracrine system for regulating Ca2+ transport.